2018
DOI: 10.1371/journal.pone.0209485
|View full text |Cite
|
Sign up to set email alerts
|

Inside the horn of plenty: Leaf-mining micromoth manipulates its host plant to obtain unending food provisioning

Abstract: Leaves represent the main resource for herbivorous insects and their performances are mainly a function of leaf nutritional quality. Two feeding strategies are known to optimize the exploitation of leaf resources: leaf-miners that selectively feed on tissues of high nutritional quality and gall-inducers that induce the development of a new tissue showing an enhanced nutritional value. Some leaf-miners are known to also manipulate their nutritional environment, but do not affect plant development. Cases of call… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 28 publications
0
22
1
Order By: Relevance
“…We propose that when the influence of gall insects reaches farther from the local vicinity of the gall that competition becomes increasingly relevant as a selective force that can shape the strength and direction of interactions with other herbivorous species. It is likely that revisiting nutrient allocation between various sinks through mass spectrometry imaging (Kaspar et al, 2011), tracing experiments, and manipulating sink strength with transplantation experiments and killing (Guiguet et al, 2018) will provide insight on the role of competition in the ecology and evolution of the endophagous lifestyle.…”
Section: Competitionmentioning
confidence: 99%
See 1 more Smart Citation
“…We propose that when the influence of gall insects reaches farther from the local vicinity of the gall that competition becomes increasingly relevant as a selective force that can shape the strength and direction of interactions with other herbivorous species. It is likely that revisiting nutrient allocation between various sinks through mass spectrometry imaging (Kaspar et al, 2011), tracing experiments, and manipulating sink strength with transplantation experiments and killing (Guiguet et al, 2018) will provide insight on the role of competition in the ecology and evolution of the endophagous lifestyle.…”
Section: Competitionmentioning
confidence: 99%
“…Species in the genus Buccalatrix (Bucculatricidae) move from leaf miners to external leaf feeders, while some gracilariids combine two different endophytic habits ( Caloptilia , Parornix ), feeding as miners for the first few instars and then become leaf folders ( Hering, 1951 ; Nakadai and Kawakita, 2016 ). Other gracilariids first feed as leaf miners and then become gall inducers, and this transition involves hypermetamorphosis of mouthparts ( Guiguet et al, 2018 , 2019 ; Guiguet, 2019 ).…”
Section: Endophytic Taxamentioning
confidence: 99%
“…This includes changes in biosynthesis of jasmonic acid, salicylic acid, abscisic acid or cytokinins (Giron et al, 2016;Zhang, 2017). Such changes can positively affect the nutritive value of the tissue the leaf-miner feeds on and can hamper the direct and indirect chemical defences of the host (Zhang et al, 2016;Guiguet et al, 2018). For example, apple plants infested with Phyllonorycter blancardella emit less sesquiterpenes than healthy ones (Vogler et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Leaf-miners induce cytokinins (CKs), phytohormones that regulate plant growth and affect senescence (Zhang et al, 2018). Recently, it was shown that a certain leaf-mining species (Borboryctis euryae: Gracillariidae) is able to actively induce callus proliferation (Guiguet et al, 2018). Consequently, such a manipulation can hamper direct and indirect chemical defences of the plant (Giron et al, 2007).…”
Section: Vo C Trappingmentioning
confidence: 99%
“…The R. fascians pathosystem is a model for the interplay between plant-and antagonist-produced molecules. The R. fascians strain D188 has a number of essential Virulence genes, which are typically (Schultz et al, 2019) Establish the boundaries of the galler's zone of influence on plant cell growth and development Compare processes plants use to make galls vs callus tissue (Sugiyama, 2018;Guiguet et al, 2018) Compare processes plants use to enhance localized growth (e.g. galls) vs overall growth Compare the plant's style of defense against gallers vs necrotrophs or other biotrophs Are plants really better at suppressing de novo growth than animals?…”
Section: Leafy Galls Made For Rhodococcus Fasciansmentioning
confidence: 99%